Effectiveness of an audio‐visual aid on the knowledge of school teachers regarding the emergency management of dental injuries. Issue 4 (12th June 2018) - Niviethitha, Sabarinathan; Bhawarlal, Chanram; Ramkumar, Hemalatha; Dhakshanamoorthy, Senthil; Shanmugam, Hariharan
Abstract: Background/Aim: Traumatic dental injuries (TDI) occur frequently in the school environment. Many studies have shown that teachers' knowledge on the emergency management of TDI is inadequate. The aim of this study was to evaluate the knowledge level among schoolteachers in Chennai, India, regarding TDI using a questionnaire and to evaluate the effectiveness of a newly developed audio‐visual aid (AV) as an educational tool by reapplying the questionnaire. Methods: The questionnaire was distributed to 345 teachers in 15 randomly selected schools. A pro forma document along with the questionnaire surveyed the teachers' demographic details and their knowledge regarding the emergency management of TDI. Then, a video containing evidence‐based information about the emergency management of TDI in accordance with the American Academy of Pediatric Dentistry (AAPD) guidelines was played for the participants. The questionnaire was readministered to test the teachers' knowledge after they viewed the video. Results: In total, 301 teachers responded to the questionnaire. Wilcoxon's signed‐rank test/chi‐square test showed that, after the teachers viewed the video, their knowledge had significantly improved relative to the handling of TDI ( P < .0001). Their attitude towards the AV aid was positive, and all participants (100%) found the AV helpful. Almost 99.7% of the participants reported increased confidence in handling dental injuries. Conclusion: There is a substantial lack of basic knowledge regarding the emergency TDI management among schoolteachers. The proposed AV aid is an effective tool for providing management strategies.